CONSIDERATIONS CONCERNING FOREIGN DIRECT INVESTMENTS IN ROMANIA, PERIOD 2011-2019 - Florentina Cristina BALDAN; Emilia UNGUREANU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2020)
The paper “Considerations concerning foreign direct investments in Romania, period 2011-2019” aims at studying which the main types of foreign direct investments were, differentiated according to the contribution of the flow of foreign equity investments in foreign direct investment companies: greenfield, mergers and acquisitions, company development, company restructurings, in the analysed period.